Cross-country adaptation and feasibility of an evidence-based resistance training intervention in the school setting - Hartman, Caroline R.; Lubans, David R.; Christiansen, Lars B. (Frontiers in Sports and Active Living, 2024)
Background: Physical activity that strengthens muscles and bones at least three times per week are recommended, but few adolescents meet this target. The aim of our study was to adapt and evaluate the feasibility and preliminary efficacy of the Australian school-based Resistance Training for Teens (RT4T) program, in Danish lower secondary schools. Methods: Developed and evaluated in Australia, the aim of RT4T is to provide adolescents with competence, confidence, knowledge, and motivation to participate in resistance training. Translation and adaptation were based on the PRACTIS-guide and involved workshops with physical education teachers. Three 7th-grade classes and three 9th-grade classes were recruited for the feasibility study and followed the program over eight weeks. Participants completed a push-up test, a standing long jump test, and a beep-test before and after the intervention. In addition, they completed a survey about their self-efficacy, motivation, and resistance training competency. Four qualitative interviews were performed with participants and their physical education teachers. Results: The participating teachers were motivated for the program, but they had difficulties providing students with appropriate feedback. Students were motivated by the equipment, games, and their improvements in fitness, but motivation declined during the program. A total of 57 students completed the physical tests and answered the survey.Resistance training self-efficacy improved significantly, while most other measures improved over time, without reaching significance. Conclusion: Overall, the RT4T was acceptable and feasible in lower secondary schools in Denmark, but adjustments need to be made to increase the reach and efficacy of the program.